2010
DOI: 10.1007/s11104-010-0418-y
|View full text |Cite
|
Sign up to set email alerts
|

Rice-maize systems of South Asia: current status, future prospects and research priorities for nutrient management

Abstract: Rice (Oryza sativa L.) and maize (Zey mays) are grown in 3.5 million hectares (Mha) in Asia that includes 1.5 Mha in South Asia. These crops are grown in sequence on the same land in the same year either in double-or triple-crop systems to meet the rice demand of a rapidly expanding human population and maize demand of livestock and poultry. The objective of this review is to provide a comprehensive overview of the current state of technical knowledge on agroecosystems and adaptation, area and distribution, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(122 citation statements)
references
References 21 publications
3
117
1
1
Order By: Relevance
“…These events can cause defoliation and Blodging,^where the crop is knocked down by the wind, breaking stems, injuring roots, and lowering yield. Waterlogging can also result, spurring root degeneration and disease (Timsina et al 2010). Compared to other loweryielding cereals or pulses, maize also requires increased seed and nutrient investments, heightening farmers' risk exposure relative to less capital-intensive crops.…”
Section: Study Region and Risk Contextmentioning
confidence: 99%
“…These events can cause defoliation and Blodging,^where the crop is knocked down by the wind, breaking stems, injuring roots, and lowering yield. Waterlogging can also result, spurring root degeneration and disease (Timsina et al 2010). Compared to other loweryielding cereals or pulses, maize also requires increased seed and nutrient investments, heightening farmers' risk exposure relative to less capital-intensive crops.…”
Section: Study Region and Risk Contextmentioning
confidence: 99%
“…A large amount of K is absorbed from rhizospheric soil through roots and it plays crucial role in antagonistic and synergistic interaction with other essential nutrients of required for crops (Zhang et al, 2010). Timsina et al, (2010) observed that even with the recommended levels of nutrient application, there is continuous gap between nutrients removal to nutrient applied in soil under different cropping systems. Continuous intensive cropping, low K application and heavy mining of K results into declining in available K in soils under long-term fertilizer experiments (Sharma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Crop rotation between flooded rice and a nonflooded maize is becoming increasingly popular, as it saves irrigation water and provides a cash crop (maize) in addition to the food crop (rice) (Timisina et al 2010). Previous studies on rice-planted flooded soil showed that the microbial community in rhizospheric soil was different from that of unplanted bulk soil (Breidenbach et al 2016b), while the difference between the microbial communities in rhizospheric soil from flooded rice and non-flooded maize was relatively small (Breidenbach and Conrad 2015).…”
Section: Introductionmentioning
confidence: 99%